T1DBase: update 2011, organization and presentation of large-scale data sets for type 1 diabetes research - Oliver S. Burren; Ellen Adlem; Premanand Achuthan; Mikkel Christensen; Richard Coulson; John A. Todd (2010)
T1DBase ( http://www.t1dbase.org ) is web platform, which supports the type 1 diabetes (T1D) community. It integrates genetic, genomic and expression data relevant to T1D research across mouse, rat and human and presents this to the user as a set of web pages and tools. This update describes the incorporation of new data sets, tools and curation efforts as well as a new website design to simplify site use. New data sets include curated summary data from four genome-wide association studies relevant to T1D, HaemAtlas—a data set and tool to query gene expression levels in haematopoietic cells and a manually curated table of human T1D susceptibility loci, incorporating genetic overlap with other related diseases. These developments will continue to support T1D research and allow easy access to large and complex T1D relevant data sets.